THE INFLUENCE OF MANAGERIAL OWNERSHIP, INSTITUTIONAL OWNERSHIP, AND COMPANY SIZE ON RETURN ON ASSETS AT PT ASTRA INTERNATIONAL Tbk - Fredy Andito; Marliza, Yayuk; Kusnadi Yudha Wiguna (Universitas Ratu Samban, 2025)
Abstract The aim of this research is to determine the influence of managerial ownership, institutional ownership and company size on return on assets at PT Astra International Tbk. This research includes quantitative associative research. The data used is secondary data in the form of PT Astra International Tbk's financial reports for 2015- 2022 which were obtained via www.astra.co.id. The results of testing the research hypothesis at the 95% confidence level show that managerial ownership, institutional ownership and company size have no effect on return on assets (ROA). Likewise, simultaneously, managerial ownership, institutional ownership and company size have no effect on ROA with a coefficient of determination of 7.4%.